2018
DOI: 10.1002/anie.201810960
|View full text |Cite
|
Sign up to set email alerts
|

A Multi‐Doped Electrocatalyst for Efficient Hydrazine Oxidation

Abstract: We report an efficient electrocatalyst for the oxidation of hydrazine,apromising fuel for fuel cells and an important analyte for health and environmental monitoring. To design this material, we emulated natural nitrogen-cycle enzymes,f ocusing on designing ac ooperative,m ulti-doped active site.T he catalytic oxidation occurs on Fe 2 MoC nanoparticles and on edge-positioned nitrogen dopants,a ll welldispersed on ah ierarchically porous,g raphitic carbon matrix that provides active site exposure to mass-transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 37 publications
2
55
0
Order By: Relevance
“…S2b. The XRD data of FeDy@MOF-Ni, Fe@MOF-Ni, and Dy@MOF-Ni match well with the diffraction peaks of Dy2O3 (JCPDS: 43-1006) [24,25] and Fe2O3 (JCPDS: 39-1346). The crystal structure of MOF-Ni was gradually destroyed during the FeDy@MOF-Ni synthesis due to ion exchange resulting in structural deformation [26,27].…”
Section: Crystallinity and Microstructural Analysessupporting
confidence: 63%
“…S2b. The XRD data of FeDy@MOF-Ni, Fe@MOF-Ni, and Dy@MOF-Ni match well with the diffraction peaks of Dy2O3 (JCPDS: 43-1006) [24,25] and Fe2O3 (JCPDS: 39-1346). The crystal structure of MOF-Ni was gradually destroyed during the FeDy@MOF-Ni synthesis due to ion exchange resulting in structural deformation [26,27].…”
Section: Crystallinity and Microstructural Analysessupporting
confidence: 63%
“…Hydrazine is avery promising liquid fuel candidate for fuel cells due to its high theoretical electromotive force (1.56 V), high power density,a nd environmentally benign byproducts [25] (Figure 3a). Hydrazine is avery promising liquid fuel candidate for fuel cells due to its high theoretical electromotive force (1.56 V), high power density,a nd environmentally benign byproducts [25] (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…In control experiments, it is demonstrated that commercial nanostructured Se powder (SEM and XRD characterizations were provided in Figure S22) has no electroactivity for HzOR; N‐doped porous carbon membrane without Se doping (NCM‐1000, structural characterizations were provided in Figure S23,24) has negligible HzOR activity, which reflected by a very high onset peak potential (0.6 V vs. RHE) and low peak current intensity (5.6 mA cm −2 ). The electrochemical active surface area (ECSA) of SeNCM‐1000 was determined to be 1175 cm 2 by double layer capacitance method (Figure S25), which is two orders of magnitudes higher than that of NCM‐1000 (57.5 cm 2 ). This investigation suggests that the existence of atomically dispersed Se could dramatically enhance the ECSA of SeNCM‐1000 thereby exhibiting outstanding catalytic activity toward HzOR.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the practical applications of the newly designed materials, we directly utilized SeNCM‐ x as electrodes without the need of a binder for HzOR. Hydrazine is a very promising liquid fuel candidate for fuel cells due to its high theoretical electromotive force (1.56 V), high power density, and environmentally benign byproducts (Figure a). The cyclic voltammetry (CV) curves of SeNCM‐ x exhibited obvious oxidation peaks in 1 m KOH solution with 100 m m N 2 H 4 , but no peaks in the pure KOH solution (Figure b).…”
Section: Resultsmentioning
confidence: 99%